If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + x * 4 + -144 = 0 Reorder the terms for easier multiplication: X + 4x + -144 = 0 Reorder the terms: -144 + X + 4x = 0 Solving -144 + X + 4x = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '144' to each side of the equation. -144 + X + 144 + 4x = 0 + 144 Reorder the terms: -144 + 144 + X + 4x = 0 + 144 Combine like terms: -144 + 144 = 0 0 + X + 4x = 0 + 144 X + 4x = 0 + 144 Combine like terms: 0 + 144 = 144 X + 4x = 144 Add '-4x' to each side of the equation. X + 4x + -4x = 144 + -4x Combine like terms: 4x + -4x = 0 X + 0 = 144 + -4x X = 144 + -4x Simplifying X = 144 + -4x
| -p+5=25-6p | | -5(k-3)=-90 | | 3g+17=5 | | .75*80= | | 2-x=-5(x-2) | | 4f-3=13 | | -3+2x=-(4-x) | | 2sin(x)-3=-2 | | 5d-7=23 | | 7=2x^2+6x+7 | | -3(5+3x)=4x-2 | | B+8=1 | | -.7x+26.9=-x+29 | | 10-x+6x=-x-4x | | -22=-6+k | | 24+8x=40 | | X^2+kx-k+8=0 | | -22=-6+6 | | 3(x+6)=2(3x+15) | | -7x+26.9=-x+29 | | 1in=6ft | | 10(b-8)-4+3b= | | 3c-1=20 | | 6+3x=-12-4x | | 3X+4=5Y+1 | | 3(x+2)-12=5(x+1) | | 11-4x=6-5x+4 | | 9xy-13=40 | | 3y+84=7x | | 6(-3b-3)+6=-120 | | 9x+7(x+12)=-6x-9(2x+4) | | log(x)-0.5(log(x+4))-1=0 |